La religión y el origen de la cultura occidental - Dawson, Christopher, 1889-1970; Andrés Gallego, José, 1944-; Vela, María Elena; Dawson, Christopher, 1889-1970. (Madrid : Encuentro, 2010)
An essential work of European history, this classic study sweeps from the fall of Rome to the dawn of the Renaissance as it shows how Christianity, its leaders, and its institutions changed the face of Western culture.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed August 19, 2016)
Keywords: Christian civilization; Civilization, Western; Electronic books